2020
DOI: 10.1021/acsabm.0c00237
|View full text |Cite
|
Sign up to set email alerts
|

Inexpensive and Versatile Paper-Based Platform for 3D Culture of Liver Cells and Related Bioassays

Abstract: The present study delineates the fabrication of paper-based devices for culturing liver cells and developing related bioassays. The devices were prepared by conventional lab-based LaserJet printing technology and employed for 3D cell culture. Our results demonstrated that the devices efficiently supported the growth of multiple cell types incuding HepG2, HUVEC, fibroblasts, and MSCs. We further showed that the device specifications (grade of paper or design parameters) greatly impacted the functional phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 68 publications
(121 reference statements)
2
28
0
Order By: Relevance
“…56 Similarly, iPSC-derived cardiomyocytes exhibited spontaneous beating functions only when seeded print paper or filter paper. Agarwal et al 52 and Dermutz et al 59 demonstrated that alterations in cellular behavior occurs as a function of paper pore size; paper scaffolds with smaller pore sizes restrict cells to the matrix surface, whereas those with greater pore sizes support cell infiltration to the core. These observations highlight the importance of understanding the dynamic interplay between the cells and the inherent properties (biochemical and biophysical) of paper matrices in a cell-specific and tissuespecific manner.…”
Section: Paper-based Cell Culture Platform: Selecting the Optimal Sub...mentioning
confidence: 99%
See 1 more Smart Citation
“…56 Similarly, iPSC-derived cardiomyocytes exhibited spontaneous beating functions only when seeded print paper or filter paper. Agarwal et al 52 and Dermutz et al 59 demonstrated that alterations in cellular behavior occurs as a function of paper pore size; paper scaffolds with smaller pore sizes restrict cells to the matrix surface, whereas those with greater pore sizes support cell infiltration to the core. These observations highlight the importance of understanding the dynamic interplay between the cells and the inherent properties (biochemical and biophysical) of paper matrices in a cell-specific and tissuespecific manner.…”
Section: Paper-based Cell Culture Platform: Selecting the Optimal Sub...mentioning
confidence: 99%
“…28 Hydrophobic barriers are also a means by which fluidic channels can be created, concentration gradients can be generated, 27,60 and/or cell behavior can be modulated (i.e., in response to alterations in the design specifications). 52 Furthermore, hydrophobic barriers also improve the portability of the paper devices (especially under the wet conditions). Among these strategies described are wax printing, LaserJet printing, Teflon printing, hot embossing, PDMS stenciling, and photolithography.…”
Section: Paper-based Cell Culture Platform: Defining the Patterns On ...mentioning
confidence: 99%
“…The functionalization of this system with photoluminescent 2-amino-2-methyl-1-propanol quantum carbon dots showed a limit of detection of 1.2 ÎŒM Cr 6+ , below the maximum allowable limit for drinking water. Recently, it was shown that functional amino-modification of cellulose-based paper scaffolds with either PAMAM (Agarwal et al 2018) or APTES (Agarwal et al 2019(Agarwal et al , 2020a, significantly improved the adhesion and spreading of the human hepatocellular carcinoma cells, HepG2. Interestingly, the degree of functionalization critically modulated the cytotoxicity and adhesion properties of the scaffolds.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Other strategies have been developed to detect and explain the biological roles of MAOs, 29 such as radiometry, liquid chromatography and mass spectrometry, enzyme-linked immunosorbent assay (ELISA), and fluorometric assay, 1,30−33 although these detection methods require expensive instruments and entail cumbersome detection processes. 34 Much work has been done to translate clinical testing into a simple and efficient format of paper-based detection platforms, 35,36 which was first shown by Whitesides. 37 Paper-based detection platforms with lightweight and low cost can be used for analyzing the single-or multiple-test samples by semiquantitating or quantitating assays.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Much work has been done to translate clinical testing into a simple and efficient format of paper-based detection platforms, , which was first shown by Whitesides . Paper-based detection platforms with lightweight and low cost can be used for analyzing the single- or multiple-test samples by semiquantitating or quantitating assays.…”
Section: Introductionmentioning
confidence: 99%